Stability studies of potent opioid analgesic, morphine‐6‐O‐sulfate in various buffers and biological matrices by HPLC‐DAD analysis. (24th March 2017) - Yadlapalli, Jai Shankar K.; Albayati, Zaineb A.F.; Penthala, Narasimha R.; Hendrickson, Howard P.; Crooks, Peter A.
Abstract: The 6‐ O‐ sulfate ester of morphine (M6S) has previously been shown to be an analgesic with greater potency and fewer side effects than morphine. However, being a sulfate ester derivative of morphine, the question exists as to whether this compound is stable in biological fluids and tissues with regard to pH‐ and esterase‐mediated degradation. To date, no studies have focused on the stability profile of M6S across the physiologically relevant pH range of 1.2–7.4. In addition, the stability of M6S is not known in rat plasma and rat brain homogenate, or in simulated rat gastric and intestinal fluids. This study determines the stability profile of M6S (utilized as the sodium salt) and demonstrates that M6S is highly stable and resilient to either enzymatic‐ or pH‐dependent hydrolysis in vitro .